Quality of life in patients with resectable rectal cancer during the first 24 months following diagnosis. (26th September 2020) - Walming, S.; Asplund, D.; Bock, D.; Gonzalez, E.; Rosenberg, J.; Smedh, K.; Angenete, E.
Abstract: Aim: An increasing number of patients survive rectal cancer, resulting in more patients living with the side‐effects of the treatment. Exploring quality of life before and after treatment enables follow‐up and additional treatment to be adjusted to the patient's needs. The aim of the study was to describe the quality of life during the 24 months following diagnosis and to identify risk factors for poor quality of life. Method: This is a prospective cohort study of patients with rectal cancer followed up by extensive questionnaires. Patients from 16 surgical departments in Denmark and Sweden from 2012 to 2015 were included. The self‐assessed quality of life was measured with a seven‐point Likert scale. Results: A total of 1110 patients treated with curative intent were included, and the response rate at the 24‐month follow‐up was 71%. Patients with rectal cancer assessed their quality of life before start of treatment as poorer than that of a reference population. At the 12‐ and 24‐month follow‐up, the quality of life on group level had recovered to the same level as for the reference population. Risk factors for poor quality of life included bother with urinary, bowel and stoma function. A reference population was used for comparison. Conclusion: The quality of life of patients with resectable rectal cancer recovered to levels comparable to a reference population 12 and 24 months after diagnosis. Our results indicate that the urinary, bowel and stoma function has an impact on quality of life.